2014
DOI: 10.1111/iej.12342
|View full text |Cite
|
Sign up to set email alerts
|

Potential for nosocomial transmission of Enterococcus faecalis from surfaces in dental operatories

Abstract: The origin of E. faecalis in secondary root canal infections remains unclear, as the potential for nosocomial transmission of enterococci from environmental surfaces in dental surgeries appears to be very small. The incorrect or ineffective disinfection procedures in general dentistry clinics needs to be addressed to counteract the risk for bacterial transmission in dental operatories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Also, the possibility of nosocomial transmission in dental clinics was highlighted due to the robust nature of the microorganisms, which have been shown to resist desiccation for months (21). It was concluded that the potential for nosocomial transmission of enterococci from environmental surfaces in dental surgeries although small, required further investigation (13).…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the possibility of nosocomial transmission in dental clinics was highlighted due to the robust nature of the microorganisms, which have been shown to resist desiccation for months (21). It was concluded that the potential for nosocomial transmission of enterococci from environmental surfaces in dental surgeries although small, required further investigation (13).…”
Section: -Discussionmentioning
confidence: 99%
“…Zehnder & Guggenheim, 2009 (12), proposed foodborne transmission, but evidence for this could not be provided in the study of Vidana et al 2016 (1) where a large number of oral and food isolates were profiled. In a separate study, the same research group concluded that whilst the potential for nosocomial transmission of enterococci from environmental surfaces in dental surgeries appeared small, further investigation of this was warranted (13).…”
Section: Introductionmentioning
confidence: 99%
“…The long‐standing concept that root canal infections with enterococci are endogenously acquired from the commensal flora has therefore been questioned, and it also seems unlikely that endodontic isolates, in analogy to hospital settings, are nosocomially transmitted from clinical high‐touch surfaces during a root canal treatment (Vidana et al . , ). The high prevalence in endodontic secondary infections and the true origin of endodontic E. faecalis thus remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…), it was also stated recently that the potential for nosocomial transmission of enterococci during the course of a root canal treatment appears to be negligible (Vidana et al . ). A narrative review by Zehnder & Guggenheim () concluded that E. faecalis was not among the early invaders of the necrotising root canal system and that E. faecalis bacteria are probably transient, originating in food.…”
Section: Discussionmentioning
confidence: 97%
“…Speculation about the origins of E. faecalis in secondary infections ranges from the presence of undetectable levels of E. faecalis in primary infections, the contamination of the root canal system with E. faecalis during or after root canal treatment (Penas et al 2013), to anachoresis. Although no proof has been found for an endogenous source of E. faecalis (Vidana et al 2011, Penas et al 2015, it was also stated recently that the potential for nosocomial transmission of enterococci during the course of a root canal treatment appears to be negligible (Vidana et al 2015). A narrative review by Zehnder & Guggenheim (2009) concluded that E. faecalis was not among the early invaders of the necrotising root canal system and that E. faecalis bacteria are probably transient, originating in food.…”
Section: Discussionmentioning
confidence: 99%